From New Deal Liberal to Supreme Court Conservative: The Metamorphosis of Justice Sherman Minton - David N. Atkinson (Washington University Law Quarterly, 1975)
Justice Sherman Minton served on the Supreme Court from 1949 to 1956. He was the eighty-seventh person to sit on the Court and the first from the state of Indiana. While Minton clearly was not a Justice of major stature, his development from politician to jurist deserves study. Much of the evidence presented in this Article points to the value of a theory of judicial role in offering plausible explanations of certain aspects of Minton’s behavior as a Supreme Court Justice. Thus an attempt, however limited, is made to explain as well as describe judicial behavior.
Keywords: Civil rights; Biography; Sherman Minton 1890-1965; United States -- Supreme Court